Analisis Peranan Komoditi Jagung terhadap Perekonomian Wilayah di Lombok Tengah (Jurnal Agribisnis dan Agrowisata, 2025)
Analysis of the Role of Maize Commodities in the Regional Economy in Central Lombok. Maize is one of the world's most important food crops besides wheat and rice. Central Lombok Regency is the highest corn producer in NTB Province. The purpose of this study: (1) To analyze whether the corn commodity is a base in the Central Lombok region, (2) To analyze the amount of regional revenue of Central Lombok Regency from corn commodities, (3) To analyze the role of corn commodities in regional development in Central Lombok. This research uses secondary and primary data. Data collection was done by documentation and analyzed by location quotient, acceptance and shift share methods. The results showed that corn commodity is a basic commodity with LQ value
Keywords: Maize; location quotient; regional income; shift share